Multistimuli-responsive multicolor solid-state luminescence tuned by NH-dependent switchable hydrogen bonds - Zhang, Rui; He, Li-Hua; Liu, Sui-Jun; Liao, Jin-Sheng; Wen, He-Rui; Chen, Jing-Lin; Zhao, Feng (Dalton transactions : an international journal of inorganic chemistry, 2023)
Revealing the stimuli-responsive mechanism is the key to the accurate design of stimuli-responsive luminescent materials. We report herein the multistimuli-responsive multicolor solid-state luminescence of a new dicopper( i ) complex [{Cu(bpmtzH)} 2 (μ-dppa) 2 ](ClO 4 ) 2 ( 1 ), and the multistimuli-responsive mechanism is clarified by investigating its four different solvated compounds 1 ·2CH 3 COCH 3 ·2H 2 O, 1 ·2DMSO·2H 2 O, 1 ·4CH 3 OH, and 1 ·4CH 2 Cl 2 . It is shown that luminescence mechanochromism is associated with the breakage of the hydrogen bonds of bmptzH-NH with counter-ions such as ClO 4 − induced by grinding, while luminescence vapochromism is attributable to the breaking and forming of hydrogen bonds of dppa-NH with solvents, such as acetone, dimethylsulfoxide, and methanol, caused by heating and vapor fuming. In addition, those results might provide new insights into the design and synthesis of multistimuli-responsive multicolor luminescent materials by using various structure-sensitive functional groups, such as distinct N-H ones, to construct switchable hydrogen bonds. Stimuli-responsive multicolor solid-state luminescence is tuned by NH-dependent switchable hydrogen bonds, in which luminescence vapochromism and mechanochromism are associated with hydrogen bonding with dppa-NH and bpmtzH-NH, respectively.